CAPTURING ZEITGEIST ON CYBER LITERATURE: A CASE OF @NKCTHI ON INSTAGRAM - Emma Natasha Octoveria; Natrila Femigasari; Nadia Athali (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
The advancement of technology, particularly the internet, has given cyber literature a prominent public recognition for its wide availability online and it has also acquired a place among the world of literature. Using the concept of zeitgeist proposed by Krause and relating it to the cyber literature on Instagram with the cultural phenomenon that is happening in Indonesia in 2018-2019, this research aims to address these questions: (1) why Instagram becomes the zeitgeist of cyber literature and (2) how Nanti Kita Cerita tentang Hari Ini (NKCTHI) reflects the zeitgeist of cyber literature on Instagram. Other than that, by considering Yongqing, Pignanolli, and Hayles’ works on digital media and cyber literature, this research found that the proliferation of cyber literature does not diminish printed literature. Instead, by investigating the phenomenon of the rising popularity of NKCTHI in Instagram, this research came to what Yongqing has suggested that cyber literature complements printed literature. Keywords: cyber literature, instagram, zeitgeist, NKCTHI Seiring dengan perkembangan teknologi internet, sastra siber yang dapat dengan mudah diakses khalayak ramai secara daring mulai mendapat tempat di dunia kesusastraan. Menggunakan konsep zeitgeist yang dibahas oleh Krause, penelitian ini bertujuan untuk memahami fenomena sastra siber di Instagram dengan mengaitkannya dengan fenomena kultural yang terjadi di Instagram di Indonesia pada periode tahun 2018-2019, untuk menjawab pertanyaan: (1) mengapa Instagram dapat menjadi zeitgeist dari sastra siber dan (2) bagaimana Nanti Kita Cerita tentang Hari Ini (NKCTHI) mewakili zeitgeist dari sastra siber yang ada di Instagram. Selain itu, merujuk pada penelitian yang sudah dilakukan oleh Yongqing, Pignanolli, dan Hayles, hasil penelitian ini menemukan bahwa adanya sastra siber tidak serta merta menghapus keberadaan sastra tradisional dalam bentuk cetak. Alih-alih, seperti yang Yongqing telah paparkan, dengan menyelidiki fenomena populernya NKCTHI di Instagram, penelitian ini berkesimpulan bahwa sastra siber melengkapi sastra tradisional yang telah ada. Kata Kunci: sastra siber, instagram, zeitgeist, NKCTHI